STAYCATION AS A NEW TRAVEL TREND IN MAJOR CITIES OF VIETNAM DURING THE COVID-19 PANDEMIC - Lê, Việt Hà (Trường đại học văn hóa Hà Nội, 2023)
Abstract. The term <<staycation» is a symbiosis of two concepts: «stay» and «vacation>> (stay + vacation). In a broad sense, the concept is suitable for a more detailed examination of the sights of one country, which is especially important in the context of the Covid-19 pandemic, when travel around the globe is limited. Vietnam is like a precious box with a surprise - each region, city is able to offer tourists exclusive features. Based on the actual situation in the tourism sector in the major cities of Vietnam, the article suggests some solutions for promoting this type of tourism among the population for its development and effective existence in the tourism business.